Food Waste Mitigation Strategy Hotel X in West Java - Nadine Diaz Salsabila; Woro Priatini; Purna Hindayani (Gastronomy Tourism Journal, 2023)
The generation of food waste in hotels is inevitable and the amount is uncertain despite the hotel's preventive measures. Food waste has a negative and detrimental impact on the hotel business because it makes more costs in purchasing and producing food so that a mitigation strategy is needed to minimize food waste generation. The research was conducted at four-star hotel X in West Java. This research aims to produce a prevention strategy to reduce food waste in hotels. The method used was qualitative. Data collection techniques include interviews, observations, and documentation studies. The results showed that the average food waste generated by hotels every day reached 128 kg. With this high number, action is needed to reduce food waste. Strict hotel regulations make food waste management options limited. Therefore, consistency in implementing mitigation strategies and openness and commitment from the hotel to make policies related to food waste are needed.